Analisis Peranan UMKM dalam Meningkatkan Ekspor: Tinjauan Kajian - Dzulfikar Al Faruq; Nuvia Kurnia Sari; Riftya Sandy (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study examines the role of Micro, Small and Medium Enterprises (MSMEs) in increasing exports with a focus on the contributions and challenges faced by MSMEs in the current context of economic globalization. The descriptive analysis method is used to identify factors that influence MSME participation in international markets. The results show that MSMEs play an important role in the expansion of a country's foreign trade, although they also face various obstacles such as access to global markets and competition with large companies. This research provides in-depth insight into the strategies needed to strengthen the contribution of MSMEs to the global economy.